Shared care planning in people with cognitive disorders and dementia: a survey among patients and caregivers in Italy - Corinna Porteri; Giulia Ienco; Edda Mariaelisa Turla; Mariassunta Piccinni; Patrizio Pasqualetti (BMC Medical Ethics)
Abstract Background There is wide convergence in the positions of scientific societies, patient associations and public bodies regarding the advisability of advance care planning (ACP) in cognitive disorders and dementia to respect the specificity of the person. Nevertheless, planning in advance for dementia represents a unique challenge. In Italy, law n. 219/2017 introduced ACP for the first time at the regulatory level, under the name of shared care planning (SCP). Few surveys on the law implementation have been conducted in Italy, but none have specifically involved patients with cognitive disorders and their caregivers. To contribute filling the gap, we conducted a survey among patients and caregivers attending a memory clinic to investigate what their knowledge, attitudes and experiences were regarding SCP. Methods We developed two semi-structured questionnaires for patients and caregivers organized into the following sections: (i) knowledge of the law; (ii) general attitude on SCP; (iii) experience about SCP; (iv) attitude about realizing a SCP; (v) advance directives. Participation in the survey was offered to consecutive patients discharged from the memory clinic during 26 target weeks and to their caregivers. The interviews were conducted on the occasion of the last scheduled visit to the facility; telephone interview was also provided. Information was collected by means of an online platform (Google Forms). Descriptive and basic inferential analysis was performed by means of SPSS (IBM). The analysis of the open-ended questions was also conducted with the support of the Voyant Tools. Results Sixty-six patient and 65 caregiver interviews were collected. No participant reported that a doctor has ever talked to the patient about SCP. The large majority of patients (85%) and almost all caregivers (95%) agree/absolutely agree with the opportunity for patients to realize SCP. Almost all participants agree/absolutely agree with the usefulness for the patients of indicating a trusted person to act on their behalf (91% patients and 95% caregivers). Forty-three (65%) patients and 48 (74%) caregivers believe it would be good to start SCP with the patient when the time is right. Among them, 20 caregivers and 12 patients believe it is already time to talk about SCP. Conclusions Study results showed patients’ and caregivers’ interest in the SCP process and, at the same time, their mixed attitude when SCP is referred specifically to themselves or their loved ones. This indicates the need to introduce the discourse on SCP into clinical practice while remaining very sensitive to the individual patient’s pace and wishes, including his/her possible refusal to talk about SCP.